Verbal Taboos in Acehnese Language: Meaning, Function, and Euphemism - Jamaluddin Nasution; Mhd. Pujiono; Muhammad Iqbal (Randwick International of Education and Linguistics Science Journal, 2023)
This research is aimed to list verbal taboo of Acehnese language and to explain reasons behind then to create a model of language revitalization as well as to propose the pattern of euphemism in maintaining norms and values to minimize language conflict. The research is qualitative description in which the data was taken by recording technique, note-taking technique on the conversations of residents at the location in Banda Aceh. The findings of the research are taboo words in Acehnese language, they are: 1) Bodies and their effluvia (toh èk replaced to jak u likôt, lagèe èk leubô should be unsaid/unspoken); 2) The organs and acts of sex, micturition and defecation (boh krèh, aneuk tét should be unsaid/unspoken, mik/mom replaced gunong); 3) Diseases, death and killing including hunting and fishing (maté replaced to meuninggai, ka geutinggai geutanyoe, ka geuwoe bak Allah, lé that eungkôt replaced to na rezeki uroe nyoe, cacar replaced to sakét mangat) ; 4) Naming, addressing, touching and viewing persons and sacred beings, objects and places (du replaced to ayah/abu/abi/bapak, ma relapced to mak/umi/mami/bunda, kah replaced to kak/cupo/da, nan replaced to aduen/abang/bang, macut/makcék, mawa, deumi Allah should be unsaid/unspoken, aneuk haramjadah should be unsaid/unspoken, buya replaced to teungku waki, tikôh replaced to nyak ti/po ti, rimueng replaced to nèk/yah nek/rumpoe tempat, gajah replaced teungku rayek); and 5) Food gathering, preparation and consumption (it is not found). This study implies to create the euphemism formulas in avoiding language conflict, then the study of taboo is not seen just only from linguistical aspect but also from culture and human’s habit by discussing taboos from sociolinguistic as well as pragmasemantic.